The Influence of Self-Efficacy, Social Media, and Financial Literacy on The MSMEs Performance in Cirebon City - Mubarokah, Ummi; Refanza Ginting, Marchielo; Mulyatno, Roni (Apollo: Journal of Tourism and Business, 2025)
MSMEs sector become the most dominant sector in Indonesian economic structure due to its contribution to Gross Domestic Product (GDP). Currently, MSMEs often experience difficulties in adapting to technology, inability to manage finances, and low self-confidence in managing a business. This research aims to determine the extent of self-efficacy, social media, and financial literacy can influence the MSMEs performance. The population in this study is micro, small, and medium enterprises (MSMEs) are located in Cirebon City. Purposive sampling is a technique used to calculate the minimum sample that can be processed using the Slovin‘s formula. This is a quantitative research study using primary data of 100 samples. The data is analyzed through multiple linear regression, along with f-test, t-test, and the coefficient of determination (R2). The result of the research show that social media and financial literacy have a significant effect on the MSMEs performance, while self-efficacy does not affect the MSMEs performance. The findings is expected to contribute to MSME actors to focus more on enhancing their digital and financial capacities to encourage business growth.